GAMBARAN STATUS GIZI PENDERITA HIPERTENSI DI PUSKESMAS REJOSARI KECEMATAN TENAYAN RAYA KOTA PEKANBARU - Muhammad Fadil; Safri Safri; Wasisto Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Nutritional status is one of the risk factors that can affect hypertension. The development of hypertension is strongly influenced by many factors. Among them are body mass index, neck circumference, waist circumference and hip waist circumference ratio. The purpose of the study was to determine the nutritional status of hypertensive patients at Puskesmas Rejosari in Pekanbaru City. This study uses quantitative methods with descriptive research designs. This research was conducted in the Puskesmas Rejosari work area with a sample of 40 people. The instrument used in this study is the observation sheet. The results of data analysis found that the age distribution of the majority of the final elderly respondents was 17 respondents (42.5%). The majority of respondents' gender distribution were women with 25 respondents (62.5%). The previous distribution of work of the respondents was mostly housewives with 16 respondents (40%). The last of education of the respondents who graduated from elementary school was the number of 17 respondents (42.5%), and the majority of respondents had a nutritional status of as many as 20 respondents (50%). The results of this study are expected to be input for the Puskesmas, to improve the nutrition program at the Puskesmas to provide nutritional information about hypertensive patient Keywords: nutritional status, hypertension patients